CROUZON SYNDROME - CLINICAL-EVOLUTIVE PARTICULARITIES. CASE REPORT - Aniko Maria Manea; Nicoleta Kiritescu; Dobre Mihaela; Mariana Boia (Amaltea Medical Publishing House, 2016)
The Crouzon's Syndrome is a rare genetic disorder, with an incidence between 1/25,000 to 1/100,000 newborn babies, transmitted autosomal dominant, characterized by facial dysmorphism and craniosynostosis, based on those characteristic can be diagnosed early. We present the case of a premature newborn female admitted to the Hospital Division of Neonatology "Louis Ţurcanu" with facial dysmorphism. The anamnestic investigation revealed that the patient's mother and sister suffer from the same type of affection. The patients affected by Crouzon Syndrome have a normal lifespan, and 97% of them have a normal intelligence. The quality of their life is affected by aesthetic considerations and the severity of abnormalities they present.